2022
DOI: 10.15252/msb.202211081
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking AlphaFold ‐enabled molecular docking predictions for antibiotic discovery

Abstract: Efficient identification of drug mechanisms of action remains a challenge. Computational docking approaches have been widely used to predict drug binding targets; yet, such approaches depend on existing protein structures, and accurate structural predictions have only recently become available from AlphaFold2. Here, we combine AlphaFold2 with molecular docking simulations to predict protein-ligand interactions between 296 proteins spanning Escherichia coli's essential proteome, and 218 active antibacterial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 54 publications
3
79
0
Order By: Relevance
“…Other methodologies, including algorithms for stability prediction and definition of search space for mutagenesis, can be refined with the help of AlphaFoldproduced structures (Zhang Y. et al, 2021). A recent report indicates that an AlphaFold-generated structure can be of sufficient quality to allow structure-based design since the predicted protein-ligand complexes were indistinguishable from their experimentally-determined counterparts (Wong et al, 2022). In June 2022, the AlphaFold team released 200 million protein structures (https://alphafold.ebi.ac.uk/), which essentially covers all catalogued proteins, significantly increasing the number of protein structures available.…”
Section: Discussionmentioning
confidence: 99%
“…Other methodologies, including algorithms for stability prediction and definition of search space for mutagenesis, can be refined with the help of AlphaFoldproduced structures (Zhang Y. et al, 2021). A recent report indicates that an AlphaFold-generated structure can be of sufficient quality to allow structure-based design since the predicted protein-ligand complexes were indistinguishable from their experimentally-determined counterparts (Wong et al, 2022). In June 2022, the AlphaFold team released 200 million protein structures (https://alphafold.ebi.ac.uk/), which essentially covers all catalogued proteins, significantly increasing the number of protein structures available.…”
Section: Discussionmentioning
confidence: 99%
“…In these contexts, ML approaches are used to improve scoring functions of binding affinity and plausible docking poses [121] , [116] , [81] , [138] , [139] . Indeed, [140] show that computationally predicted structures perform on par with experimental structures at reverse docking tasks - although the docking and scoring methods themselves could use major improvements to further drug discovery and design.…”
Section: Machine Learning In the Protein Fieldmentioning
confidence: 99%
“…Wong et al used 12 essential proteins, 218 active compounds, and 100 inactive compounds to predict antibacterial inhibitors and found that, although models had low performance, the use of rescoring strategies may have acceptable predictive power for certain proteins. They concluded that the limitations in benchmarking are not due to the AlphaFold structures itself, but to the methods to accurately model the protein-ligand interactions [27]. Other studies have identified potential inhibitors of WD40 repeat and SOCS box containing 1 protein (WSB1), a clinically relevant drug target, by means of AlphaFold and virtual screening approaches [28].…”
Section: Structural Data Determinationmentioning
confidence: 99%
“…They found that rescoring based on simplistic knowledgebased scoring functions, e.g., measuring interaction fingerprints, appears to outperform modern machine learning methods, highlighting the importance of the use of rescoring methods to properly detect the most potent binders [103]. Similarly, recent studies have demonstrated that the use of machine learning approaches to rescore docking poses greatly enhances the performance of structural models and that ensembles of rescoring functions increase prediction accuracy [27]. They concluded that the use of empirical data to assess docking predictions is a key factor to improve the prediction of protein-ligand interaction in drug discovery.…”
Section: Computational Approaches Based On Structural Data: Virtual S...mentioning
confidence: 99%